Math, asked by cgaya, 9 months ago

2 + root 3/2- root 3​

Answers

Answered by alpeshnco
0

your questions incomplete

Answered by anindyaadhikari13
1

Given to rationalise,

 \sf \frac{2 +  \sqrt{3} }{2 -  \sqrt{3} }

 \sf =  \frac{2 +  \sqrt{3} }{2 -  \sqrt{3} }  \times  \frac{2 +  \sqrt{3} }{2 +  \sqrt{3} }

 \sf =  \frac{ {(2 +  \sqrt{3} )}^{2} }{ {(2)}^{2}  -  {( \sqrt{3}) }^{2} }

 \sf =  \frac{4 + 3 + 2 \sqrt{6} }{4 - 3}

 \sf = 7 + 2 \sqrt{6}

which is the required answer.

Similar questions